2021
DOI: 10.1088/1755-1315/905/1/012119
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants used for treating urinary tract problems in eastern Indonesia

Abstract: Indonesia is one of the wealthiest countries in biological resources that have potential as medicinal plants. Medicinal plants can be an alternative in treating diseases such as urinary tract problems by the people of eastern Indonesia. The study aims to evaluate the use of medicinal plants for various urinary tract problems in east Indonesia, including their efficacy and safety based on the literature review. This research was conducted by interview method and field survey. The data were collected from tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…It has been reported to have similar use in Yogyakarta and Vietnam (Nahdi and Kurniawan 2019;Nguyen et al 2019). The use of O. aristatus to treat urinary tract infections is in line with the research of Nisa et al (2021), who found that O. aristatus is the plant most often used to treat urinary tract infections in several areas of eastern Indonesia.…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported to have similar use in Yogyakarta and Vietnam (Nahdi and Kurniawan 2019;Nguyen et al 2019). The use of O. aristatus to treat urinary tract infections is in line with the research of Nisa et al (2021), who found that O. aristatus is the plant most often used to treat urinary tract infections in several areas of eastern Indonesia.…”
Section: Discussionsupporting
confidence: 74%
“…Other used plant parts include fruits, bark (7% each), and seeds (4%). Similarly, leaves are the most common plant part used in Iran (Bahmani et al 2016), Burkina Faso (Kam et al 2018), and Indonesia (Nisa et al 2021) to treat UTIs. The use of leaves in herbal remedies is mainly due to easy accessibility and because they are the seat of photosynthesis and preferential sites for accumulating active ingredients (Mukaila et al 2023).…”
Section: Plant Parts Usedmentioning
confidence: 99%
“…2 In Indonesia, knowledge of the efficacy and safety of medicinal plants is typically based on empirical experiences passed down through generations rather than scientific testing. 3 For the legal health services to be increased, it is necessary to make research efforts on a medicinal plan so that the drug can be rugged safely and effectively. 4 One plant in the Zingiberaceae family that is widely used as a medicinal plant is ginger.…”
Section: Introductionmentioning
confidence: 99%